Aramejska wersja Księgi Sofoniasza - Kuśmirek, Anna (Collectanea Theologica, 2018)
The chief aim of this article is to show the key features of the Aramaic version of the Book of Zephaniah, that is a part of the Targum Jonathan. The first section of the research discusses the most important aspects of the theological concepts of Targum Jonathan based on examples from Targum Zephaniah. The second part of the article also presents some features of targumic renderings.